Sistem Pendukung Keputusan Pemilihan Santri Terbaik Tahfidzh Qur’an Pada Yayasan Islamic Center Menggunakan Metode VIKOR - Alfina Mutiara (STMIK Budi Darma, 2020)
Santri is a term for someone who follows Islamic religious education in a place called a pesantren, the students will follow a schedule of study and worship that has been arranged in such a way and is mandatory for students to carry out until education is complete. In the decision-making process, it requires a system change from the old system, which partly still uses or is still manual, to the new system. Given the large number of students who will be selected among the students, the number of which is in the hundreds of people, so that the selection department really finds it difficult to select the best prospective students. For this reason, it is necessary to have a decision support system in producing decisions so that it can support the decisions made by the Islamic Center Foundation in a more real way. In this study, one of the Vise Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR) methods was used which is expected to be able to assist the Islamic Center Foundation in selecting the best tahfidzh quran students.